Comparative Analysis of Bitcoin, Stocks, and Gold Cryptocurrencies as Alternative Investment Portfolios: Analisis Perbandingan Cryptocurrency Bitcoin, Saham, dan Emas Sebagai Alternatif Portfolio Investasi - Rafly Firdaus Budiartomo; Wisnu Panggah Setiyono (Academia Open, 2023)
The purpose of this research is to find out and analyze the comparison of the performance of bitcoin cryptocurrency, stocks, and gold. The population in this study is the monthly closing price of bitcoin, LQ45 shares, and gold from January 2018 - December 2020, which is 252 datas. The sampling technique of this research is saturated samples. The analytical method used is the comparative method and the data used are secondary data. Data is calculated using the Microsoft Excel program based on the formula of each variable. The data was processed statistically using the SPSS application, the Kruskall-Wallis Test. The results of this study indicate that there is no significant difference between bitcoin, LQ45 stocks, and gold when measured from return and Jensen's performance measure. Then, there are significant differences between bitcoin, LQ45 stocks, and gold when measured from risk, Sharpe performance’s measure, and Treynor’s performance’s measure. Highlights: Bitcoin, stocks, and gold: Comparative performance analysis Highlighting the comparison of performance between bitcoin, LQ45 stocks, and gold. Investigating the differences in performance measures such as return, Jensen's measure, risk, Sharpe's measure, and Treynor's measure. Sample and analytical methods Utilizing saturated samples and secondary data for the study. Employing the Kruskall-Wallis Test to analyze the data statistically. Results: Performance similarities and differences No significant difference observed between bitcoin, LQ45 stocks, and gold in terms of return and Jensen's performance measure. Significant differences identified when considering risk, Sharpe's performance measure, and Treynor's performance measure among bitcoin, LQ45 stocks, and gold. Keywords: Bitcoin, LQ45 stocks, gold, performance comparison, Kruskall-Wallis Test